AN ERROR ANALYSIS ON STUDENTS’ WRITING ABILITY IN RECOUNT TEXT - Muhamad Ahsanu; Dewanti Ratna Pertiwi (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
This research taps the stance of error analysis (henceforth EA) projected on students’ understanding of the basicgrammatical points and their ability in composing a recount text. Therefore, this paper is concerned with thelevels of students' ability in basic grammar and the typical errors they make in their constructing recount texts.The theory utilized in this research paper drawn heavily from the standpoints of error analysis primarily byRichards and Ellis as mentioned in the theoretical framework. The error classification and procedure of erroranalysis principally replicate the frameworks proposed by both Richards (1977) and Ellis (2003).The sample isthe second grade students of SMA N 1 Kasihan Yogyakarta taken purposively. The findings depict that thestudents still make most types of grammatical errors, intralingual and developmental errors in composing theirrecount text.AbstrakPenelitian ini menitik beratkan pada analisis kesalahan atau yang dikenal dengan istilah error analysis padatingkat pemahaman siswa tentang dasar-dasar tata bahasa Inggris dan kemampuan mereka dalam menyusunsebuah naskah cerita. Teori yang digunakan dalam makalah ini terkait dengan teori analisis kesalahan yangutamanya disadur dari karya Richards and Ellis sebagaimana diuraikan pada kerangka teori. Klasifikasi kesalahandan prosedur analisis kesalahan pada prinsipnya mengikuti kerangka yang dirancang okeh Richards (1977) danEllis (2003). Adapun sampel dalam makalah ini adalah siswa-siswa tingkat 11 SMA N 1 Kasihan Yogyakartayang diambil secara purposive. Temuan akhir penelitian ini menunjukkan bahwa tipe kesalahan yang palingsering dibuat oleh siswa-siswa tersebut mencakup kesalahan tata bahasa, kesalahan intralingual dan kesalahanpengembangan dalam membuat teks cerita.